Foldamers to Nanotubes: Influence of Amino Acid Side Chains in the Hierarchical Assembly of α, γ4‐Hybrid Peptide Helices. Issue 50 (24th October 2014) - Jadhav, Sandip V.; Misra, Rajkumar; Gopi, Hosahudya N.
Abstract Supramolecular assembly of various artificially folded 12‐helical architectures composed of γ4‐Val, γ4‐Leu and γ4‐Phe residues is investigated. In contrast to the 12‐helices composed of γ4‐Val and γ4‐Leu residues, the helices with γ4‐Phe residues displayed unique elongated nanotubular architectures. The elongated nanotube assembly was further explored as a template for biomineralization of silver ions to silver nanowires. A comparative study using an analogous α‐peptide helix reveals the importance of the spatial arrangement of aromatic side chains along the helical cylinder in a 12‐helix. These results suggested that the proteolytically and structurally stable α, γ4‐hybrid peptide 12‐helices may serve as a new generation of potential templates in the design of functional biomaterials.